Bacterial cellulose production, functionalization, and development of hybrid materials using synthetic biology - Vadanan, Sundaravadanam Vishnu (2022)
Bacterial cellulose (BC) has been utilized as a biopolymer matrix for various applications. The advancement of synthetic biology has brought new approaches for its production and functionalization. In this mini-review, we briefly discuss the conventional methods to improve BC production and functionalization, and their challenges. We summarize the application of synthetic biology to address these challenges and its use to develop novel hybrid living materials. Finally, we consider the opportunities and future prospects of synthetic biology in bioengineered materials.